2022
DOI: 10.1039/d1dt03653j
|View full text |Cite
|
Sign up to set email alerts
|

Sr3B14O24: a new borate with a [B14O30] fundamental building block and an unwonted 2D double layer

Abstract: A new alkaline-earth metal borate, Sr3B14O24, was successfully synthesized by high temperature solution method. It crystallizes in the monoclinic space group P21/c (No. 14) and features a fundamental building block...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 68 publications
1
6
0
Order By: Relevance
“…45 In the previous research, few fluoroaluminoborates with excellent optical properties have been reported, and they have been listed in Table S4 in the Supporting Information. As shown in Figure S1 in the Supporting Information, the similar edge-sharing octahedra can be found in other fluoroaluminoborates 60,61 In addition, there are also some successful cases of various structural motif linkers filled in the single-layer structures. 39,40 As far as we know, the [Al 2 B 6 O 14 F 4 ] unit as a structural motif linker filled in interlamination of double-layer structure in Sr 2 Al 2.18 B 5.82 O 13 F 2 is the first case in borates, which greatly enriches the structural chemistry of layered borates.…”
supporting
confidence: 63%
See 1 more Smart Citation
“…45 In the previous research, few fluoroaluminoborates with excellent optical properties have been reported, and they have been listed in Table S4 in the Supporting Information. As shown in Figure S1 in the Supporting Information, the similar edge-sharing octahedra can be found in other fluoroaluminoborates 60,61 In addition, there are also some successful cases of various structural motif linkers filled in the single-layer structures. 39,40 As far as we know, the [Al 2 B 6 O 14 F 4 ] unit as a structural motif linker filled in interlamination of double-layer structure in Sr 2 Al 2.18 B 5.82 O 13 F 2 is the first case in borates, which greatly enriches the structural chemistry of layered borates.…”
supporting
confidence: 63%
“…Moreover, the [Al 2 B 6 O 14 F 4 ] units are filled in the interlamination to replace the bridging oxygen and used to connect the two 2 ∞ [Al 1.18 B 2.82 O 8 ] layers to construct 2 ∞ [Al 4.36 B 11.64 O 26 F 4 ] double layers. Based on the thorough survey, varied structural motifs filled in interlamination of double-layer structures can be found in borates (Figure S2 in the Supporting Information), such as bridging O/F in Cs 2 Al 2 (B 3 O 6 ) 2 O and K 3 N 3 Li 2 Al 4 B 6 O 20 F (N = Sr, Ba), , [BO 3 ] units in CsBaB 9 O 15 and RbMT 3 (BO 3 ) 2 O 3 (M = Ba, Sr; T = Al, Ga), , [B 2 O 5 ] units in M 2 Cd 3 B 16 O 28 (M = Rb, Cs) and Cs 2 K 2 B 10 O 17 , , [B 3 O 7 ] units in PbLnB 7 O 13 (Ln = Tb or Eu), [B 9 O 18 ] units in Na 11 B 21 O 36 X 2 (X = Cl, Br), 1 ∞ [B 6 O 12 ] infinite chains in AgSrB 7 O 12 and Sr 3 B 14 O 24 . , In addition, there are also some successful cases of various structural motif linkers filled in the single-layer structures. , As far as we know, the [Al 2 B 6 O 14 F 4 ] unit as a structural motif linker filled in interlamination of double-layer structure in Sr 2 Al 2.18 B 5.82 O 13 F 2 is the first case in borates, which greatly enriches the structural chemistry of layered borates.…”
mentioning
confidence: 99%
“…SrB 4 O 7 shows wide transparency band, large NLO coefficients, high optical damage threshold and excellent mechanical strength [26] . Several recent examples of strontium borates are Sr 3 B 6 O 11 (OH) 2 ( P 1 ${\bar{1}}$ ), [27] Sr 3 B 14 O 24 ( P 2 1 / c ), [28] Sr 4 B 10 O 18 (OH) 2 ⋅ 2H 2 O ( P 1), [29] Sr 2 B 5 O 9 (OH) ⋅ H 2 O ( C 2), [30] and Sr 2 [B 6 O 9 (OH) 4 ] ( P 2 1 ) [31] . Different polyborate anions from [B 5 O 12 ] 9− to [B 14 O 30 ] 18− are observed in these strontium borates.…”
Section: Introductionmentioning
confidence: 99%
“…The exception was the thermal expansion of γ-and α-Ca2B2O5 modifications: polymorphic transitions of Ca2B2O5, and the crystal structure of the high-temperature polymorph was determined from powder HTXRD data at 600 °С [50]. Therefore, one of the goals of this work was to study the thermal expansion of Caborates and the unique triple-layered Sr-borate solved recently [60].…”
Section: Introductionmentioning
confidence: 99%